Efeito da administração de deslorelina na indução de estro em cadelas no anestro - Leonardo Lara e Lanna (2008)
The efficacy of an injectable formulation of deslorelin (a GnRH agonist) was evaluated to induce estrus in anestrous bitches, with one or multiple deslorelin doses. Thirteen animals composed three groups: Group 1 (n=5, single IM injection of 2,0mg of deslorelin), Group 2 (n=5, four IM injections of 2,0mg of deslorelin in alternate days) and Control Group (n=3, four IM saline injections in alternate days). Daily clinical evaluations, sexual behavior, vaginal cytology, plasma progesterone concentration, ovaryhysterectomy and macroscopic evaluation of the uterus and ovaries were done. In Group 1 none of the bitches showed signs of estrus, while two developed clinical signs and vaginal cytology of proestrus. In Group 2 all animals presented proestrus, four presented estrus and three ovulated, resulting in a functional corpus luteum, and high progesterone concentration until day 25 of diestrus, when ovaryhysterectomy was performed. The duration of the stages of deslorelin induced cycles and the progesterone profile were similar to those described in the literature, and no side effects were observed. In conclusion, deslorelin injectable formulation in multiple injections was effective to induce fertile estrus in anestrous bitches